Pola Komunikasi Interpersonal Guru dan Anak Penyandang Disabilitas Tunagrahita Kelas IX SLB C Muzdalifah Medan dalam Meningkatkan Kemandirian - Husna Imama; Suheri Harahap; Muhammad Faishal (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This study aims to determine the pattern of interpersonal communication between teachers and children with intellectual disabilities in class IX SLB C Muzdalifah Medan in increasing independence. This research uses SOR (Stimulus-Response) theory. The method used is descriptive qualitative and data collection techniques used include interviews, observation and documentation. The results showed that the pattern of interpersonal communication between teachers and children with intellectual disabilities in class IX at SLB C Muzdalifah Medan was using a lecture pattern (explanation pattern), question and answer pattern and media pattern. In addition to communication patterns, there is also a communication process carried out between the two, namely using the primary communication process and the secondary communication process. While the interpersonal communication patterns of teachers and students with mental retardation in class IX SLB C Muzdalifah Medan in increasing independence use self-reliance and self-development patterns. By applying a good pattern, the pattern of interpersonal communication between teachers and children with disabilities, especially mental retardation, goes well, effectively and competently.